TINGKAT KELANGSUNGAN HIDUP DAN PERTUMBUHAN UDANG VANAME (Litopanaeus vannamei) PADA SALINITAS 0 PPT DENGAN METODE AKLIMATISASI BERTINGKAT MENGGUNAKAN KALSIUM CaCo3 - Nurhasanah Nurhasanah; Muhammad Junaidi; Fariq Azhar (Jurnal Perikanan Unram, 2021)
In shrimp cultivation, high production activities can cause serious water quality problems. One way that can be done is by transferring cultivation containers with a method of decreasing salinity to 0 ppt with the addition of calcium (CaCO3) as a user balancing the life of cultivated shrimp in order to survive. The purpose of the study was to analyze the survival rate and growth of vaname shrimp (Litopanaeus vannamei) maintained at salinity 0 ppt with multilevel acclimatization method using lime (CaCo3). This study consisted of five treatments, and each treatment had 3 repeats. Thus in this study there were 15 experimental units. As treatment is the difference in acclimatization period decreases salinity as follows: Treatment 1: No decrease in salinity (30 ppt). Treatment 2: Acclimatization for 2 days (30 ppt, 0 ppt) using calcium. Treatment 3: Acclimatization for 3 days (30 ppt, 15 ppt, 0 ppt) using calcium. Treatment 4: Acclimatization for 4 days (30 ppt, 20 ppt, 10 ppt, 0 ppt) using calcium. Treatment 5: Acclimatization for 5 days (30 ppt, 23 ppt, 15 ppt, 8 ppt, 0 ppt) using calcium. The results showed that shrimp acclimatized with tiered use of lime (CaCO3) resulted in absolute weight growth which is a range of 0.45-0.72 grams, absolute long growth which is a range of 3.03-3.81 cm, FCR values that are 0.89-1.85 and survival rates that are 74.67-100%. The conclusion of this study is that the decrease in salinity with the stratified acclimatization method using lime (CaCO3) had no real effect on absolute weight growth, absolute length growth, feed conversion rate, survival rate.